Web Accessibility Analysis of Massive Open Online Courses in Mathematical Disciplines - E. A. Kosova; M. Yu. Khalilova (Высшее образование в России)
The paper studies the problem of developing the massive open online courses (MOOCs) that conform to the content accessibility principles for persons with disabilities. Using the browsing of MOOCs platform catalogues, a total of 56 Russian-language free MOOCs in mathematical disciplines hosted on 5 platforms has been received. By automatic testing using Web Accessibility Checker, the accessibility of the functional and informational content of the MOOCs was evaluated. 73% of MOOCs were found to conform to the syllabus subjects “Probability Theory and Mathematical Statistics”, “Discrete Mathematics” and “Algebra and Geometry”; 8 basic disciplines of higher mathematics education are not covered by online education; 96,4% of the courses have accessibility limitations, especially for people with visual impairment. Accessibility problems are related to shortcomings of the platforms and MOOC developers’ errors. The results show a weak coverage by MOOCs of the basic mathematical disciplines included in the higher education curriculum in Russia and indicate the low content accessibility of the mathematical MOOCs for students with disabilities. The results of the work imply the need for: expanding the range of MOOCs to cover all basic mathematical disciplines; troubleshooting the accessibility in existing courses (pursuant to WCAG); prescription to platforms and developers to strictly adhere to WCAG in future courses.